PENINGKATAN KESEJAHTERAAN EKONOMI MELALUI USAHA BATIK TULIS; PEMBERDAYAAN PEREMPUAN OLEH PESANTREN KANZUN NAJAH KOTA BATU - Eko Raharto (LPPM STAI Muhammadiyah Probolinggo, 2026)
Islamic boarding school-based women's empowerment through hand-drawn batik businesses is a strategic effort to improve the economic welfare of the community. The Pesantren utilizes the potential of hand-drawn batik to promote economic independence and strengthen women's roles. This study aims to analyze the model and role of women's empowerment in improving economic welfare through hand-drawn batik businesses run by the Pesantren Kanzun Najah in Batu City. The research method used descriptive qualitative research with an instrumental case study approach, using primary and secondary data sources. Informants were selected using purposive sampling, with 11 informants, consisting of Islamic boarding school leaders and members, as criteria for empowerment members. The results show that women's empowerment is implemented through a gradual and participatory empowerment model, encompassing three stages: (1) socialization and awareness-raising, (2) hand-drawn batik training, and (3) ongoing mentoring. This model enables women to acquire batik technical skills and increases self-confidence. Empowerment plays a role in improving economic welfare, while strengthening women's independence and role in family economic decision-making. However, empowerment still faces challenges such as limited skills, unstable production, and dependence on mentoring from Islamic boarding school administrators. On the other hand, there are significant opportunities for developing hand-drawn batik businesses through the product's cultural value or regional characteristics, Islamic boarding school support, and sustainable access to promotion.